Nonsingular Modules Over Serial Rings - Manish Kumar Jha (Mathematical Statistician and Engineering Applications, 2019)
Non-Singular Modules over serial rings are equivalent to Modules with a unique in decomposable decomposition. They form closed subset of the module lattice. The ring of endomorphism of non-singular modules is serial ring.